Causal agent of anthracnose in the pea crop (Pisum sativum L.) in northern of Perú: Symptomatology, isolation and identification, pathogenicity and control - Aguilar, René (2021)
Pea (Pisum sativum L.) is an economically important crop and of great demand in the national and international market, due to the considerable number of families that depend on its cultivation, especially in the northern and central highlands of Peru. However, the anthracnose is one of the limiting factors for low productive and causes economic losses. The aim of this study was to describe the symptoms, culturally and morphometrically identify the causal agent and to evaluate under in vitro the efficacy of fungicides. Isolation was made from samples of leaves and pods with anthracnose symptoms collected in the crop field. Healthy pea was used in the pathogenicity test, and discs of PDA medium containing isolated fungi were inoculated into them. The poisoned food technique was used, and colony growths were measured to evaluate the effects of fungicides. The results based on the symptoms, morphological and cultural characteristics described, the isolates were identified as Colletotrichum lindemuthianum, C. truncatum y Ascochyta pisi, which was confirmed with Koch's postulates. Trifloxystrobin+tebuconazole was found to be the most effective fungicide followed by tebuconazole, procloraz and mancozeb completely inhibited mycelial growth (100%) of identified fungi. These results are useful for the control of Colletotrichum lindemuthianum, C. truncatum y Ascochyta pisi in the pea crop.